Does green finance matter for sustainable entrepreneurship and environmental corporate social responsibility during COVID-19?. Issue 2 (19th August 2021) - Sadiq, Muhammad; Nonthapot, Sakkarin; Mohamad, Shafi; Chee Keong, Ooi; Ehsanullah, Syed; Iqbal, Nadeem
Abstract : Purpose: The discourse aimed to investigate green finance practices under the assumptions of several notable climate advisors and speculators in Asia and particularly in Southeast Asia. The study intrigues by considering financial specialists to vent government spending on green restoration plans leading toward green bankable venture openings for the public and private sector. This section distinguishes a few of the green fund components and approaches that can be joined by national and neighborhood governments, essentially in Southeast Asia, into their post-COVID-19 techniques, but are too valuable inputs for domestic commercial banks and private corporates. Design/methodology/approach: It can be defined as a functional type for Cobb Douglas development. ARDL technology is a way of calculating complex forces at the classification level at long-term and short-term stages. This ARDL approach has many advantages and can be implemented when incorporated in level I (0) and level I first (1) with the original variable. Still, it offers robust ability to the outcomes and standardizes the lag, considering the number and sample size used. Pooled mean group (PMG) method is becoming a convenient technique for monitoring data over the period and a good approach for energy impact panels – growth ties for creating links between energy emissions and environmental sustainability and businesses in the nation. Findings: There is a positive partnership between creativity and a sustainable world. Corporations are recommended to uphold the principles of CSR in the development process by introducing environmentally friendly advanced technologies. The main objectives of corporate social responsibility (CSR) are economic growth, environmental sustainability and social justice. Several programs have been established to expand businesses' responsibilities to improve their confessions in sustainable growth. SMEs are a primary source of production of innovative products and technologies. The key concerns of stakeholders and politicians in the new competitive business climate are the protection of environmental sustainability and social responsibility, recognizing factors driving economic development for SMEs. Originality/value: During the COVID-19 era, the prime responsibility of pandemic confronting governments is to spend on help activities (that have been started in earlier phase) and recovery endeavors (yet to start in the situation). Therefore, the governments may devise policies to pool resources from commercial, private, public-private partnerships and other capital market sources. With rising hazard recognitions particularly emerging from at-threat income projections, governments ought to make the correct mechanisms and instruments that can perform this catalytic part of derisking and drawing in such capital. This too can be an opportunity for governments to enhance and execute such financial instruments that offer assistance, quicken their commitments to climate alter beneath the Paris Agreement and the sustainable development goals (SDGs), and thus "build back better" is being progressively voiced over the world.